Cultivating curiosity teaching and learning reimagined - Nelson, Doreen G. (Jossey-Bass, a Wiley imprint, 2022)
"Cultivating Curiosity: Teaching & Learning Reimagined outlines the provenance of the Doreen Nelson Method of Design-Based Learning and how to apply it in today's K-12 classrooms. Part master class and part memoir, this book shows the reader the professional journeys of many of the thousands of teachers, now, last year, and across the decades, who have transformed their teaching practice by applying Design-Based Learning. This is more than a "how-to" book. It is inspirational as well as instructive and serves as a roadmap and rallying cry for all those yearning to break away from formulaic teaching. It is told from personal perspectives--the author's and others--and backed up by years of quantitative and qualitative data. The book will include three sections: The Doreen Nelson Method Of Design-Based Learning; The Dynamic Classroom; Developing a Design-Based Learning Classroom"--
Includes index. - Online resource; title from digital title page (viewed on October 07, 2021)
Keywords: Constructivism (Education) -- United States; Simulated environment (Teaching method); Active learning -- Case studies -- United States; Doreen Nelson Method of Design-Based Learning; Constructivisme (Éducation); États-Unis; Environnement simulé (Méthode pédagogique); Apprentissage par l'action; États-Unis; Études de cas; Active learning; Constructivism (Education); United States; Case studies